PENGARUH PEMBERIAN BAKING SODA TERHADAP KUALITAS MIE BASAH - Mario Syarif; I Nyoman Sukana Sabudi (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2017)
Noodles are one of the most popular food items that have a range of varieties and types in Indonesia, one of which is wet noodles. This research covers the use of baking soda to make wet noodles. The goal of this research is to discover the noodles’ qualities based on its’ flavor, aroma, texture, and color (organoleptic). The methods used in this food experimental research are organoleptic and likert scale. The results of the organoleptic tests’ flavor, aroma, texture, and color shows that the quality of wet noodles with the addition of baking soda in it is good for sample I and a very good result for sample II.